The Role of Partnership Contracts (PPP) in the Progress of Developing Countries - El-Sayed, Hoda (Journal of Legal Sciences, 2023)
This study dealt with the concept of partnership, explaining that this term, has many definitions, and included in the legislation of the majority of countries, and addressed by many scholars, researchers and thinkers.  All this is due to the importance of its role in providing the necessary financing for the establishment, implementation, development and maintenance of projects, financing from the private sector, away from the state budget, or borrowing from abroad. It explained the relationship between the partnership system and the progress of developing countries, explaining that this system provides the necessary financing for the basic projects needed by the state, from two sources, the first is a set of objectives, which works to provide financing, and the second is a set of principles, working to attract capital and provide a suitable climate for investment. In addition, the study outlined some of the characteristics of developing countries, which illustrated their strong need for financing, and some of the factors that encouraged private investment, which helped them to progress.